Does who responds matter?: exploring potential proxy response bias in the Washington Group Short Set disability estimates - Beuoy, Aaron; Goddard, Kelsey S. (Frontiers in Research Metrics and Analytics, 2025)
IntroductionThe Washington Group Short Set (WG-SS) is a widely used tool for identifying disability in national and international population-based surveys. However, results from cognitive testing revealed key differences in response patterns between individuals who self-report and those with a proxy respondent. Considering proxy reporting is frequently used in national surveys, discrepancies between reporting sources could affect the accuracy of disability prevalence estimates and have important implications for health equity and policy.MethodsA binary logistic regression was conducted to examine the relationship between proxy respondents and WG-SS disability status after controlling for sociodemographic characteristics, using pooled data from the 2010–2018 National Health Interview Survey (NHIS).ResultsAfter controlling for sociodemographic characteristics, proxy respondents were 4.48 times more likely to be classified as having a WG-SS disability compared to those who self-reported.DiscussionDifferences in proxy reporting have real implications for equity, access, and policy accountability. If proxy reporting systematically increases the likelihood of disability classification, prevalence estimates may be distorted. This is especially problematic when proxies are more likely to report for populations already at risk of under- or overrepresentation in disability data, such as older adults, people with cognitive disabilities, and children and adolescents. Future studies using the WG-SS should treat the reporting source, i.e., proxy response, not as a procedural footnote, but as a central variable in assessing data quality and equity.